# Factorize each of the following quadratic polynomials by using the method of completing the square:(i) $y^2-7y+12$(ii) $z^2-4z-12$

Given:

(i) $y^2-7y+12$

(ii) $z^2-4z-12$

To do:

We have to factorize the given quadratic polynomials.

Solution:

Factorizing algebraic expressions:

Factorizing an algebraic expression implies writing the expression as a product of two or more factors. Factorization is the reverse of distribution.

An algebraic expression is factored completely when it is written as a product of prime factors.

Completing the square is a method that is used to write a quadratic expression in a way such that it contains the perfect square.

(i) The given expression is $y^2-7y+12$.

Here,

The coefficient of $y^2$ is $1$

The coefficient of $y$ is $-7$

The constant term is $12$

Coefficient of $y^2$ is $1$. So, we can factorize the given expression by adding and subtracting square of half of coefficient of $y$.

Therefore,

$y^2-7y+12=y^2-7y+12+(\frac{7}{2})^2-(\frac{7}{2})^2$              [Since $\frac{1}{2}\times7=\frac{7}{2}$]

$y^2-7y+12=y^2-2(y)(\frac{7}{2})+(\frac{7}{2})^2+12-(\frac{7}{2})^2$

$y^2-7y+12=(y-\frac{7}{2})^2+12-\frac{49}{4}$                     (Completing the square)

$y^2-7y+12=(y-\frac{7}{2})^2+\frac{12\times4-49}{4}$

$y^2-7y+12=(y-\frac{7}{2})^2+\frac{48-49}{4}$

$y^2-7y+12=(y-\frac{7}{2})^2-\frac{1}{4}$

Now,

$(y-\frac{7}{2})^2-\frac{1}{4}$ can be written as,

$(y-\frac{7}{2})^2-\frac{1}{4}=(y-\frac{7}{2})^2-(\frac{1}{2})^2$           [Since $\frac{1}{4}=(\frac{1}{2})^2$]

Using the formula $a^2-b^2=(a+b)(a-b)$, we can factorize the given expression as,

$(y-\frac{7}{2})^2-\frac{1}{4}=(y-\frac{7}{2})^2-(\frac{1}{2})^2$

$(y-\frac{7}{2})^2-\frac{1}{4}=(y-\frac{7}{2}+\frac{1}{2})(y-\frac{7}{2}-\frac{1}{2})$

$(y-\frac{7}{2})^2-\frac{1}{4}=(y+\frac{-7+1}{2})(y-\frac{7+1}{2})$

$(y-\frac{7}{2})^2-\frac{1}{4}=(y+\frac{-6}{2})(y-\frac{8}{2})$

$(y-\frac{7}{2})^2-\frac{1}{4}=(y-3)(y-4)$

Hence, the given expression can be factorized as $(y-4)(y-3)$.

(ii) The given expression is $z^2-4z-12$.

Here,

The coefficient of $z^2$ is $1$

The coefficient of $z$ is $-4$

The constant term is $-12$

Coefficient of $z^2$ is $1$. So, we can factorize the given expression by adding and subtracting square of half of coefficient of $z$.

Therefore,

$z^2-4z-12=z^2-4z-12+2^2-2^2$              [Since $\frac{1}{2}\times4=2$]

$z^2-4z-12=z^2-4z+2^2-12-4$

$z^2-4z-12=z^2-2(z)(2)+2^2-16$

$z^2-4z-12=(z-2)^2-16$                     (Completing the square)

Now,

$(z-2)^2-16$ can be written as,

$(z-2)^2-16=(z-2)^2-4^2$                       [Since $16=4^2$]

Using the formula $a^2-b^2=(a+b)(a-b)$, we can factorize the given expression as,

$(z-2)^2-16=(z-2)^2-4^2$

$(z-2)^2-16=(z-2+4)(z-2-4)$

$(z-2)^2-16=(z+2)(z-6)$

Hence, the given expression can be factorized as $(z-6)(z+2)$.

Updated on: 12-Apr-2023

47 Views 